2017
DOI: 10.2147/ijn.s148065
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of nano-TiO<sub>2&nbsp;</sub>thin films with enhanced biocompatibility and antimicrobial activity for orthopedic implants

Abstract: Titanium (Ti) and its alloys have been extensively used as implant materials in orthopedic applications. Nevertheless, implants may fail due to a lack of osseointegration and/or infection. The aim of this in vitro study was to endow an implant surface with favorable biological properties by the dual modification of surface chemistry and nanostructured topography. The application of a nanostructured titanium dioxide (TiO 2 ) coating on Ti-based implants has been proposed as a potential wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 48 publications
(52 reference statements)
1
79
0
Order By: Relevance
“…In maxillofacial prostheses, the reduction of the incidence of tissue inflammation surrounding the prostheses has been explored by coating the surface with nanostructured TiO 2 . As a result, the introduction of nano-TiO 2 coatings has been shown to inhibit a rather large range of bacteria strains [101]. These few examples suggest that the combination of different elements into the coating is likely needed to provide a wide spectrum of anti-biofilm activity, though the role of the coating roughness has not been explored in detail.…”
Section: Antibiofilm Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In maxillofacial prostheses, the reduction of the incidence of tissue inflammation surrounding the prostheses has been explored by coating the surface with nanostructured TiO 2 . As a result, the introduction of nano-TiO 2 coatings has been shown to inhibit a rather large range of bacteria strains [101]. These few examples suggest that the combination of different elements into the coating is likely needed to provide a wide spectrum of anti-biofilm activity, though the role of the coating roughness has not been explored in detail.…”
Section: Antibiofilm Activitymentioning
confidence: 99%
“…These few examples suggest that the combination of different elements into the coating is likely needed to provide a wide spectrum of anti-biofilm activity, though the role of the coating roughness has not been explored in detail. On the other hand, investigations into the effect of individual NPs on the biofilm disruption has been obtained for Au [36,102], Ag [103], Mg [104], ZnO [42,102,105], CuO [102,106], CeO [102], Fe 3 O 4 [107], YF [108] and TiO 2 [101], indicating that smaller NPs with high surface to volume ratio have a remarkable effect on biofilm destruction [98].…”
Section: Antibiofilm Activitymentioning
confidence: 99%
“…The bio-engineering technologies of medical devices through nano-structuring and coating has recently been proposed, not only to prevent microbial adhesion, but also to improve the biocompatibility of materials [5][6][7][8] to develop the ideal orthopedic implant.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are used for TiO 2 deposition on biomaterials such as sol-gel [24,25], spin-coating [12,26], anodization [9,10,27], atomic layer deposition [28] and magnetron sputtering [11,13,[29][30][31] . Magnetron sputtering is a extensively used method as it produces films with greater adhesion, hardness and hydrophilicity [19,30,32,33], and it is also able to generate isolated phases of anatase and rutile [34].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the high variability in the test conditions used for different studies. In one hand, studies reported that TiO 2 has an antibacterial effect [8][9][10]27,28,[37][38][39][40], while on the other hand, different studies revealed no influence on early biofilm formation [9,36], highlighting the need for further studies.…”
Section: Introductionmentioning
confidence: 99%